Analysis of LoRa with LoRaWAN Technology Indoors in Polytechnic of Malang Environment - Noprianto, Noprianto; Dien, Habibie Ed; Ratsanjani, M. Hasyim; Hendrawan, Muhammad Afif (Sistemasi: Jurnal Sistem Informasi, 2024)
Technology is one of the fields heavily influenced by rapid developments, undergoing significant changes each year. One of the technologies affected is data transmission. Data transmission faces its own challenges, and each region encounters different constraints in their connections, such as the distance of data delivery. In this regard, expanding the data delivery range is crucial to optimize connections and system performance. The use of LoRaWAN for sensor monitoring in IoT devices is designed to transmit data over a wide area with low power consumption and long-term usability, thus overcoming these issues. Data collection in this study utilizes the technique of measuring RSSI (Received Signal Strength Indicator), SNR (Signal-to-Noise Ratio), and LoRa's time interval, considering distance and location parameters at Politeknik Negeri Malang and its surrounding areas. Locations chosen include each floor of the Civil Engineering building to obtain data parameters like RSSI, SNR, and time intervals, which improve when the distance between the transmitting LoRa node and the LoRa gateway gets closer. After conducting tests, it was found that using a 35 dBi antenna outperforms a 10 dBi antenna in data transmission. This was evidenced by the RSSI values approaching 0 from floor 8 to 1 in the Civil Engineering building of Politeknik Negeri Malang. Additionally, the use of a 35 dBi antenna resulted in a 50% faster data transmission compared to the 10 dBi antenna. LoRaWAN technology, particularly The Things Network, can be employed to manage LoRa. However, similar technologies like Chripstack can also be used to manage LoRaWAN more flexibly on the local network